Modelling Technology Innovation Commercialization (TICO) Activity in Academia & Industry - An Ontology - Fernando dos Santos Nogueira (2021)
Darwin had study and defended its "Theory of Evolution", which discusses natural selection and the small variations iterative process that increase the individual's ability. It is possible to say that knowledge evolves in the same way. Born within the academia, this knowledge was firstly used on pure academic activities, evolving to a practical and entrepreneurial model. Technology inventions were developed through this iterative and incremental process of knowledge creation. This is the base that nowadays, academia and industry use to create new products and services that are available for commercialization, aiming for the so called, "value creation". With this research the author focus was to create a model that could explain all this technology commercialization process, explaining the dynamic relationships that exists between the different stakeholders, as such: government, academia, industry, technology transfer office/technology licensing office (tto/tlo), researcher and many more. For this, it was intended to absorb and use the already existing knowledge base, building a concepts definition database to support the designed model. The designed Technology Innovation Commercialization ontology (TICO) builds on: a) TICO literature review; b) analysis of existing models; c) refinement of the artefact with professionals' experts and, d) a final model assessment. The global evaluation calculated by an Attribute Agreement Analysis reached a 92% of approval and at a sub-ontology level the scores were: for the High-Level 93%; for the TTO/TLO 89%; for the Researcher 86%; and, for the Industry 100%. Furthermore, the evaluation of competence questions demonstrated that all questions were answered by the ontology. The results of the ontology evaluation indicate that the TICO achieved its purpose, and it can be claimed a validation of this work. Therefore, the proposed model describes the diverse interactions that do exist and influence this technology activity, from their foundation till to its value creation impact, answering the research questions. It is expected that this approach could be the base for future studies that could deep dive in this matter with different focus and bigger information that could further validate this technology commercialization process.